Factors influencing the enrolment of female students studying civil engineering at tertiary institutations: A case study of Bulawayo Polytechnic. - Takaza, Tracy (Midlands State University, 2017)
The study investigated on the factors influencing enrolment of female students studying civil engineering. The low enrolment of female students studying civil engineering prompted the researcher to carry out the study. Research questions were highlighted and the significance of the study, delimitations of the study, limitations of the study were presented. The literature review revealed factors which influences the enrolment of female students studying civil engineering which were socio-cultural, personal and socio-economic factors. The descriptive case study was chosen because of its ability to give in-depth information about the phenomenon understudy. The population consisted of eighty students of which fifty five were male and twenty five were female students. Five lecturers also constituted the population. Simple random sampling was used to select a sample of students and purposive sampling was used to select a sample of lectures. The researcher used questionnaires and interviews to collect data. Data collected were presented and analyzed descriptively using quantitative and qualitative sampling. Research study revealed that the causes of low enrolment were lack of proper Science and Mathematical background, lack of career guidance in schools and socio-cultural factors as well as lack of role models in the society. Challenges faced by female students included social challenges, physical capabilities and financial challenges. Intervention strategies proposed were effective career guidance at secondary level, encouragement of female students to do Mathematics, Science and Technical drawing at secondary level to enhance the chances of studying civil engineering.